Pengaruh Tax Avoidance, Sales Growth, Dan Ukuran Perusahaan Terhadap Nilai Perusahaan: (Pada Perusahaan Sektor Consumer Non-Cyclicals sub Sektor Perusahaan Makanan dan Minuman di Bursa Efek Indonesia Tahun 2019 - 2023) - Habibah, Nur; Fitria Eka Ningsih (EkoPreneur, 2025)
This study aims to analyze the effect of tax avoidance, sales growth, and company size onfirm value in food and beverage companies within the non-cyclical consumer sector listedon the Indonesia Stock Exchange (IDX) during the 2019–2023 period. The totalpopulation consisted of 95 companies, and the sample was selected using a purposivesampling method based on specific criteria, resulting in 16 companies as the researchsample. With an observation period of five years, the number of observations analyzedamounted to 80. The data used were secondary data obtained from audited annual reportsand sustainability reports published between 2019 and 2023 and accessed from theofficial IDX website. The research applied an associative method with a quantitativeapproach, while the analysis technique employed statistical methods and panel dataregression using EViews 12 and Microsoft Excel software. The results of the study showthat tax avoidance, sales growth, and company size simultaneously affect firm value,confirming the collective influence of financial strategies and company characteristics onmarket perceptions. However, the partial test results reveal varied effects: tax avoidancehas a positive effect on firm value, indicating that companies implementing tax-savingstrategies tend to be perceived as more profitable and attractive to investors; sales growthhas a negative effect on firm value, suggesting that rapid expansion may createoperational risks and additional costs that reduce investor confidence; while companysize shows no significant effect, meaning that a larger scale alone does not guaranteehigher valuation in the capital market. These findings underscore the complexity ofinteractions between tax strategies, growth performance, and firm characteristics inshaping firm value, while also providing important implications for investors, regulators,and company management in developing effective strategies to strengthencompetitiveness and enhance market trust. Keywords: Tax Avoidance, Sales Growth, Company Size, Company Value